A lens ultrasonic vibration-assisted laser machining system for laser polishing and laser drilling of 304 stainless steel. (December 2021) - Kang, Di; Zou, Ping; Wang, Wenjie; Xu, Jilin; Shen, Cheng
Highlights: Processing quality improved by ultrasonic vibration-assisted laser machining. Lens ultrasonic vibration-assisted laser machining device with high flexibility. Laser energy density of the spot changed periodically by lens ultrasonic vibration. Expression of hollow ultrasonic transducer can be widely used in device design. Abstract: This paper proposes a novel lens ultrasonic vibration-assisted laser machining device which applies the ultrasonic vibration to the lens, thereby enhancing the quality of laser processing and retaining the flexibility of laser processing. The general analytical expression of the hollow ultrasonic transducer is derived by exploiting the electromechanical equivalent circuit and the four-terminal network methods. The finite element analysis method is used to optimize the design results, and the resonant frequency and ultrasonic vibration amplitude of the prototype are calibrated using testing equipment. The results show that the vibration form of the device at the mode of 23 meets the designed requirements, and the resonance frequency is 29703 Hz. Under the condition of 30000 Hz, the device reaches the maximum amplitude of 30 μm on the end face of the lens, and the corresponding input voltage is 346 V. The processing mechanism for lens ultrasonic vibration-assisted laser machining is proposed based on this study, which changes the laser energy density on the workpiece by adjusting the diameter of the spot. Furthermore, the initial experiment validation of the device shows that the ultrasonic vibration of the lens is attracting significant interest for improving the surface quality of laser polishing and reducing the taper angle of laser drilling, which is mainly caused by the change of laser energy density.